Coronavirus Related Fears among Residents of Karachi, Pakistan - Faiza, Afreen; Munazza, Aymen (Infectious Diseases Journal of Pakistan, 2022)
Objective: The emerging epidemic coronavirus (COVID-19) crisis rattled nearly every sphere of life across all over the globe, aim of the study was to explore fears produced due to the swift spread of the deadly virus among residents of Karachi city, Pakistan. Method: A 10–item Coronavirus Fear Questionnaire (CVFQ) with good reliability (a=.75, p<.01) purposely constructed based on informal interviews from the general population and administered on (N=264) participants invited via an online Google based survey. Results: Outcomes showed the prevalence of fears related to the infection to oneself (76.5%), family (84.5%), contagious transmissions (62.9%), death of loved ones (72.3%), financial constraints (80.7%), increase in prices (85.2%), disease rumors (80.7%), restriction of mobility (71.2%), and social rejections (61.7%). Conclusion: It was concluded that residents of Karachi possess different fears related to COVID-19, which warrants appropriate psychosocial attention. Key words: Coronavirus, Questionnaire, Reliability, Fears, Karachi, Pakistan